Facility-Based Maternal Death in Western Africa: A Systematic Review - Gunawardena, Nathali; Bishwajit, Ghose; Yaya, Sanni (Frontiers in Public Health, 2018)
Background For exploring maternal death, supply and demand side factors can be characterized by the three delays model developed by Thaddeus and Maine (1994). The model comprises delay in deciding to seek care (delay 1), delay in reaching the health facility (delay 2) and delay in receiving quality care once at the health facility (delay 3). Few studies have comprehensively dealt with the health systems delays that prevent the receipt of timely and appropriate obstetric care once a woman reaches a health facility (Phase III delays). The objective of the present study was to identify facility level barriers in West African health facilities. Methods Electronic databases (Medline, CINAHL, CABI Global Health, EMBASE) were searched to identify original research articles from 1996-2016. Search terms (and synonyms) related to: 1) maternal health care (e.g. obstetric care, perinatal care, maternal health services); 2) facility-level (e.g. maternity unit, health facility, Phase III, hospital); 3) Western Africa (e.g. Nigeria, Burkina Faso) were combined. This review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Results Of the 2103 citations identified, 13 studies were eligible. Studies were conducted in Nigeria, Burkina Faso, Gambia, Guinea, Senegal and Sierra Leone. 30 facility level barriers were identified and grouped into 6 themes (human resources; supply and equipment; referral-related; infrastructure; cost-related; patient-related). The most obvious barriers included staff shortages, lack of maternal health services and procedures offered to patients, and lack of necessary medical equipment and supplies in the health care facilities. Conclusions This review emphasizes that phase I and phase II barriers are not the only factors preventing women from accessing proper emergency obstetric care. Health care facilities in Western Africa are inadequately equipped to handle the obstetric needs of patients. Supply- side barriers must be addressed in order to reduce maternal mortality in the region.